Model Latihan Sirkuit Training terhadap Peningkatan Kondisi Fisik Pemain Futsal di Club ZFCA Cidahu - Cahya Lukmana; Muhammad Saleh; Ahmad Alwi Nurudin (Jurnal Educatio FKIP UNMA, 2026)
This study aims to analyze the impact of the circuit training model on improving the physical condition of futsal players at ZFCA Cidahu. The research method used a quasi-experimental quantitative approach with a One-Group Pretest-Posttest design. The research sample consisted of 20 players determined through a purposive sampling technique. Data collection instruments included a 20-meter sprint test, Illinois Agility Run Test, Standing Long Jump, Bleep Test, and zigzag dribbling test. Data were analyzed using a paired sample t-test to measure the effectiveness of the intervention over four weeks. The results showed a significant increase in all tested physical components. For the speed variable, a Sig. (2-tailed) value of 0.000 was obtained with a t-count of 8.405 > t-table of 2.093. Meanwhile, for the agility variable, there was a decrease in average travel time of 2.29 seconds with a significance of 0.000. These findings prove that systematic circuit training interventions can optimize neuromuscular adaptation and physical performance of players. It was concluded that a structured and measurable circuit training program is an effective method for improving players' physical readiness and mobility to meet the demands of high-intensity futsal matches. Keywords: Circuit Training, Physical Condition, Futsal, Agility, Speed.